Virtual hull monitoring of a naval vessel using hindcast data and reconstructed 2-D wave spectra. (May 2020) - Thompson, Ian
Abstract: A novel virtual hull monitoring approach is assessed using full-scale measurements from a naval vessel trial to address two questions. First: Can this technique accurately reproduce stress spectra from measured strains? Second: Are responses calculated using reconstructed two-dimensional wave spectra from hindcast data more accurate than those using simpler wave representations? Stresses calculated using wave hindcast data, ship track information, and stress transfer functions compare favorably to those derived from strain gauge measurements at five structural locations. Wave conditions are represented using a spectrum model along with bulk spectral parameters (significant wave height, peak period, and primary direction) from hindcast datasets and by reconstructing two-dimensional spectra from hindcast partition data. Both approaches give good agreement with strain measurements but using the more-detailed reconstructed two-dimensional wave spectra yields better results. Results suggest that wave hindcast data are sufficient for accurate structural calculations, encouraging further study of virtual hull monitoring using wave hindcast data. Highlights: Results show that accurate hull monitoring without additional instrumentation is possible but further work is required. Naval vessel trial stress spectra accurately calculated using ship track, wave hindcast data, and spectral method. Reconstructed two-dimensional wave spectra from hindcast data gave more accurate stress results than simpler spectra. Wave hindcasts provided an accurate source of wave data for this structural assessment.